A Maximal inequality of non-negative submartingale - Kim Young-Ho (Journal of Inequalities and Applications, 1999)
In this paper, we prove the maximal inequality , , between a non-negative submartingale , is strongly subordinate to and , where is real valued function such that for each , . This inequality improves Burkholder's inequality in which .